A simple and reliable method for claustrum localization across age in mice - Tarek Shaker; Gwyneth J. Dagpa; Vanessa Cattaud; Brian A. Marriott; Mariam Sultan; Mohammed Almokdad; Jesse Jackson (Molecular Brain)
Abstract The anatomical organization of the rodent claustrum remains obscure due to lack of clear borders that distinguish it from neighboring forebrain structures. Defining what constitutes the claustrum is imperative for elucidating its functions. Methods based on gene/protein expression or transgenic mice have been used to spatially outline the claustrum but often report incomplete labeling and/or lack of specificity during certain neurodevelopmental timepoints. To reliably identify claustrum projection cells in mice, we propose a simple immunolabelling method that juxtaposes the expression pattern of claustrum-enriched and cortical-enriched markers. We determined that claustrum cells immunoreactive for the claustrum-enriched markers Nurr1 and Nr2f2 are devoid of the cortical marker Tle4, which allowed us to differentiate the claustrum from adjoining cortical cells. Using retrograde tracing, we verified that nearly all claustrum projection neurons lack Tle4 but expressed Nurr1/Nr2f2 markers to different degrees. At neonatal stages between 7 and 21 days, claustrum projection neurons were identified by their Nurr1-postive/Tle4-negative expression profile, a time-period when other immunolabelling techniques used to localize the claustrum in adult mice are ineffective. Finally, exposure to environmental novelty enhanced the expression of the neuronal activation marker c-Fos in the claustrum region. Notably, c-Fos labeling was mainly restricted to Nurr1-positive cells and nearly absent from Tle4-positive cells, thus corroborating previous work reporting novelty-induced claustrum activation. Taken together, this method will aid in studying the claustrum during postnatal development and may improve histological and functional studies where other approaches are not amenable.